Implementasi Metode Forward Chaining untuk Mendeteksi Defisensi Vitamin Pada Manusia - Kurniyanti, Asshiva Fitricia; Siswanti, Sri; Setiyowati, Setiyowati (Jurnal Ilmiah SINUS, 2024)
There are many vitamins such as vitamins A, B, B1, B2, B3, B5, B6, B7, B9, B12, C, D, E, K and various symptoms that are almost similar, making it difficult to identify independently. The challenges associated with vitamin deficiency disorders include long wait times at the doctor's office or during limited working hours, as well as expensive charges. The purpose of the research is to enable the general population to identify and treat vitamin deficiencies in the body by using symptoms as a guide. The research will be conducted online to save costs and provide accessibility from anywhere at any time. In the study, there were 40 symptoms in 14 vitamins which were then applied according to the concept of Forward chaining method, namely IF-THEN rule. When a user enters answers that comply with the rules, the expert system consults with them to diagnose the problem. If the user enters answers that do not conflict with the rules, the system will display the diagnostic results, which include information and remedies for vitamin deficiencies. While literature reviews and nutritionist interviews were used as the data collection strategy, Web-based system implementation used PHP programming language, and MySQL as database media. After conducting validation tests between the system's output and expert data, the system achieved an 87.5% calculation result. It is clear from the test results that this system is operating effectively and appropriately.